COMMUNICATING BOGOR CITY AS CITY HERITAGE THROUGH SPATIAL CITY - Mariana R.A Siregar; Diana Amaliasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
City branding is an effort to build the economy of a city,country or province. Study about city branding is part of city planning that aims to build differentiation and strengthen the city brand. Bogor City as one of the cities that have the potential of its culture but still have not determined its capital brand. This research aims to find out how Bogor implement the primary communications strategy. The strategies include landscape, infrastructure, organizational structure, administration, and also culture behavior approach. Qualitataive method used to determine the most influential approach to city branding. Information gained through in-depth interviews to several stakeholders and files. This study find several outputs such as: The strategy of landscape approach and infrastructure approach mainly supported the establishment of Bogor as heritage city. Meanwhile Organization structure and administration approach as well as the culture behavior already existed, but the implementstion still not optimal and not clearly visible.